Peran Generasi Z dalam Menjaga Keseimbangan Ekologi Melalui Pendekatan Hadits Pelestarian Alam - Muhammad Iqbal Al-Azizi; Nasrulloh (Al-Kindi, 2026)
This research aims to analyze the role of Generation Z in maintaining ecological balance through understanding the hadith of nature conservation, ecological awareness, and environmentally friendly behavior practices. This study uses a qualitative approach with the type of field research. The data was obtained through in-depth interviews with Generation Z students at Maulana Malik Ibrahim State Islamic University Malang, which were analyzed in a descriptive-interpretive manner. The results of the study show that students' understanding of the hadith on nature conservation is at the substantive-normative level, although it has not been structured textually and methodologically. Hadith about planting trees, maintaining cleanliness, and excessive prohibition in the use of resources are understood as the basis for environmental ethics with religious nuances. This understanding contributes to forming an ecological consciousness that views environmental preservation as part of religious responsibility. This awareness encourages the practice of environmentally friendly behavior, both individually and collectively in the campus environment, although its consistency is still influenced by structural factors and consumption culture. This study concludes that hadith understanding, ecological awareness, and environmentally friendly behavior form interrelated relationships and need to be strengthened through contextual religious education and environmentally oriented campus policies.